2018
DOI: 10.1021/acs.iecr.8b01090
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Foamed Titania Carbon Nitride Nanocomposite and Its Synergetic Visible-Light Photocatalytic Performance

Abstract: Efficient visible-light-driven materials are key for environmental remediation. The foamed titania–carbon nitride nanocomposite (FTCN) was synthesized by in situ microemulsification followed by calcination using bulk g-C3N4 and TBOT. During calcination the bulk g-C3N4 transformed into ultrathin nanosheets. The nanocomposite is characterize by state of the art physicochemical techniques; the structure look like foam with mesoporous cavities. The carbon nitride nanosheets were uniformly distributed and mostly em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 58 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…The unique properties of nanomaterials provide opportunities for the removal of toxic metals from contaminated water system. In the literature, various nanoparticles have been reported to be used for heavy-metal removal from aqueous system. Among these nanoparticles, TiO 2 nanoparticles were utilized to remove contaminants from water. , Li et al compared the adsorption of lead ion using TiO 2 nanoparticles and TiO 2 /cellulose fiber nanocomposites and found that hybrid material adsorbed 371.0 mgg –1 compared to TiO 2 , which adsorbed 20 mgg –1 . These studies show that TiO 2 and its composites are capable to adsorb lead ions.…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties of nanomaterials provide opportunities for the removal of toxic metals from contaminated water system. In the literature, various nanoparticles have been reported to be used for heavy-metal removal from aqueous system. Among these nanoparticles, TiO 2 nanoparticles were utilized to remove contaminants from water. , Li et al compared the adsorption of lead ion using TiO 2 nanoparticles and TiO 2 /cellulose fiber nanocomposites and found that hybrid material adsorbed 371.0 mgg –1 compared to TiO 2 , which adsorbed 20 mgg –1 . These studies show that TiO 2 and its composites are capable to adsorb lead ions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the photodegradation efficiency of the BiOCl/ZnO/CN was higher than the individual components. This is attributed to the coupling of CN nanosheets into BiOCl/ZnO, which is helpful for sufficient visible light absorption and rapid charge transportation during the photocatalytic reaction . The photocatalytic activity of different reported catalysts has been provided in Table to compare the outstanding performance of novel BiOCl/ZnO/CN nanocomposite under visible light.…”
Section: Resultsmentioning
confidence: 99%
“…The pure TiO 2 sample exhibits an optical absorption response between 400 nm and 800 nm, while it can be seen that the ZnS/CdS-Mn/MoS 2 /TiO 2 nanocomposite displays the highest intensity among as-prepared materials, suggesting the improved light harvesting ability ascribed to the synergetic contact of ZnS, CdS-Mn, MoS 2 , and TiO 2 . 39 The bandgap energy could be measured by a plot of ( αhυ ) 2 versus ( hυ ) using the equation 21
Figure 4. (a) DRS spectra of sample 0: TiO 2 , 1: ZnS/TiO 2 , 2: MoS 2 /TiO 2 , 3: CdS-Mn/TiO 2 , 4: ZnS/CdS-Mn/TiO 2 , and 5: ZnS/CdS-Mn/MoS 2 /TiO 2 composite. (b) Plots of ( αhυ ) versus photon energy ( hυ ) for estimated optical bandgap of TiO 2 and ZnS/CdS-Mn/MoS 2 /TiO 2 .
…”
Section: Resultsmentioning
confidence: 99%
“…20 Therefore, great efforts have been dedicated to extending its energy spectrum from the UV (approximately 5%), that is only a small portion of the sunlight spectrum, to the visible spectral region (approximately 45%). 21 It is highly imperative to explore novel and efficient visible-light-driven photocatalysts. 22 Li et al 23 illustrated that Pt at TiO 2 could accomplish high efficiency of H 2 production with simultaneous photodegradation of eosine Y and methylene blue.…”
Section: Introductionmentioning
confidence: 99%